2005
DOI: 10.1245/aso.2005.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Sarcoma: A Challenge for the Surgeon

Abstract: RISs are aggressive malignancies with a high tendency for local recurrence and distant metastases. Previously applied treatment often hampers adequate resection. Therefore, radical surgical resection is the only chance to improve disease-free and overall survival, but it may also have a palliative role. Still, the overall prognosis remains poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 27 publications
4
51
1
1
Order By: Relevance
“…Recent studies [24,32] suggest that, with early diagnosis and aggressive medical and surgical treatment strategies, such as those adopted in our study, the survival rate of patients suffering from "secondary" sarcomas can approach that of primary sarcomas, describing a median survival of 12 months [24,32], which is similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies [24,32] suggest that, with early diagnosis and aggressive medical and surgical treatment strategies, such as those adopted in our study, the survival rate of patients suffering from "secondary" sarcomas can approach that of primary sarcomas, describing a median survival of 12 months [24,32], which is similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 88%
“…7 Similarly, RT-induced sarcomas are typically high-grade, with a tendency toward distant metastasis and local recurrence following resection. 8 The risk of secondary malignancy following RT is related to overall survival time. Travis et al showed that the relative risk of a second malignancy in survivors of testicular cancer is inversely correlated with age at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Radical surgery (R0 resection) is possible in 50% to 75% of patients who have RAS located in any part of the body and results in 5-year local relapse-free survival rates of 34% to 46% and 5-year survival rates of 27% to 44%. 7,17,31,32 A review of all 92 patients of angiosarcoma after breast-conserving therapy reported in the English literature revealed that 55 of 75 patients (73%) with at least 1 year of follow-up developed a local recurrence after mastectomy (n ¼ 72) or wide local excision (n ¼ 3). 33 In that review, all patients who received adjuvant radiotherapy (n ¼ 1) and/or chemotherapy (n ¼ 3) experienced a local recurrence.…”
Section: Discussionmentioning
confidence: 99%